Eave tubes for malaria control in Africa: prototyping and evaluation against Anopheles gambiae s.s. and Anopheles arabiensis under semi-field conditions in western Kenya - Snetselaar, Janneke (Malar J, 2017)
BACKGROUND: Whilst significant progress has been made in the fight against malaria, vector control continues to rely on just two insecticidal methods, i.e., indoor residual spraying and insecticidal bed nets. House improvement shows great potential to complement these methods and may further reduce indoor mosquito biting and disease transmission. Open eaves serve as important mosquito house entry points and provide a suitable location for intercepting host-seeking anophelines. This study describes semi-field experiments in western Kenya with eave tubes, a household protection product that leverages the natural behaviour of host-seeking malaria mosquitoes. METHODS: Semi-field experiments were conducted in two screen-houses. In both of these a typical western Kenyan house, with mud walls and corrugated iron sheet roofing, was built. Eave tubes with bendiocarb- or deltamethrin-treated eave tube inserts were installed in the houses, and the impact on house entry of local strains of Anopheles gambiae and Anopheles arabiensis was determined. Experiments with open eave tubes (no netting) were conducted as a control and to determine house entry through eave tubes. Insecticidal activity of the inserts treated with insecticide was examined using standard 3-min exposure bioassays. RESULTS: Experiments with open eave tubes showed that a high percentage of released mosquitoes entered the house through tubes during experimental nights. When tubes were fitted with bendiocarb- or deltamethrin-treated inserts, on average 21% [95% CI 18–25%] and 39% [CI 26–51%] of An. gambiae s.s. were recaptured the following morning, respectively. This contrasts with 71% [CI 60–81%] in the treatment with open eaves and 54% [CI 47–61%] in the treatment where inserts were treated with fluorescent dye powder. For An. arabiensis recapture was 21% [CI 14–27%] and 22% [CI 18–25%], respectively, compared to 46% [CI 40–52%] and 25% [CI 15–35%] in the treatments with open tubes and fluorescent dye. CONCLUSIONS: Insecticide-treated eave tubes resulted in significant reductions in recapture rates for both malaria vector species, representing the first and promising results with this novel control tool against Kenyan malaria vectors. Further field evaluation of eave tubes under more realistic field conditions, as well as their comparison with existing approaches in terms of cost-effectiveness and community acceptance, is called for. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12936-017-1926-5) contains supplementary material, which is available to authorized users.